Reviews and Responses for Uncovering Hidden Inefficiencies in the Route Availability Document - Monstein, Raphael; Krummen, Jan; Koelle, Rainer; Sáez, Raúl; Verdonk Gallego, Christian (Journal of Open Aviation Science, 2025)
Detailed reviews and responses can be found in the PDF and HTML versions of this document. The DOI for the original paper is https://doi.org/10.59490/joas.2024.7892